Essential University Physics: Volume 1 (3rd Edition)

Published by Pearson
ISBN 10: 0321993721
ISBN 13: 978-0-32199-372-4

Chapter 4 - Exercises and Problems - Page 70: 73


Please see the work below.

Work Step by Step

We know that $F-T-m_1g=m_1a$ This simplifies to: $m_1=\frac{F-T}{a+g}=\frac{30-18}{9.8+3.2}=0.92Kg$ For the other mass $T-m_2g=m_2a$ This simplifies to: $m_2=\frac{T}{g+a}$ $m_2=\frac{18}{9.8+3.2}=1.4Kg$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.